Rethinking Article 6: the criminal fair trial rights case law of the European Court of Human Rights - Goss, R (2012)
This thesis is a critique of the European Court of Human Rights’ case law on the right to a fair trial in criminal cases. It is the result of a focussed and extensive survey of Article 6 case law, and, unlike other work on Article6, does not analyse each component right of Article 6 one-by-one. Instead, the thesis considers ‘cross-cutting’ themes common to all, or many, of the Article 6 component rights: how the Court interprets Article 6, how the Court sees its role in Article 6 cases, how the Court approaches Article 6’s internal structure, the Court’s implied rights jurisprudence, and how the Court assesses alleged Article 6 violations. In considering how the Court assesses alleged violations of Article 6, the thesis charts the Court’s attempts to solve ‘the puzzle of Article 6’: how should violations of Article 6 be assessed in the absence of an express metaprinciple? In this regard the thesis examines notions such as the proceedings as a whole test, counterbalancing and defect-curing, the ‘never fair’ jurisprudence, and the extent to which the public interest may justify restrictions on Article 6. The thesis uses a rule of law framework to test the Article 6 case law for its ability to provide guidance to citizens, lawyers and officials. It argues that the case law is marked by considerable uncertainty, inconsistency, and incoherence, with the result that the ability of that case law to provide guidance is significantly undermined. Indeed, the thesis establishes that there is inconsistency and uncertainty within the various tools and approaches used by the Court, and that there is significant incoherence between those approaches. To the extent the thesis makes a normative argument, it constitutes a robust and targeted call for the Court to adopt in this area of law a renewed, rejuvenated approach that is more consistent, more coherent, and better explained.